2017
DOI: 10.12669/pjms.332.12262
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy versus middle-energy extracorporeal shockwave therapy for the treatment of snapping scapula bursitis

Abstract: Objective:Extracorporeal shockwave therapy (ESWT) has been used successfully in treatment of musculoskeletal disorders. Our objective was to assess the effectiveness of low versus middle-energy ESWT on snapping scapula bursitis.Methods:Thirty-five patients, divided into two groups, group (L), received low-energy ESWT, group (M) received middle-energy ESWT. Groups were evaluated at 1,3,6 and 12 months using the Visual Analogue Scale (VAS), the Constant-Murley scoring (CMS) and the Roles and Maudsley criteria.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Treatment of IGB focuses on symptom control. Primary treatment in IGB is lifestyle modification by avoiding physical activities or daily habits that have caused the symptoms in the first place 24 , 25 . In addition, the use of ESWT in conservative management is recommended to be beneficial in reducing adhesion in chronic bursitis by breaking down scar tissues, increasing extensibility, mobility of surrounding structure, and ultimately promoting normal orientation of collagen fibers 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of IGB focuses on symptom control. Primary treatment in IGB is lifestyle modification by avoiding physical activities or daily habits that have caused the symptoms in the first place 24 , 25 . In addition, the use of ESWT in conservative management is recommended to be beneficial in reducing adhesion in chronic bursitis by breaking down scar tissues, increasing extensibility, mobility of surrounding structure, and ultimately promoting normal orientation of collagen fibers 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…CSI achieved a mean of 37-point reduction in VAS score on a 100-point scale after 6 months of treatment, compared with a mean of 60-point reduction in VAS score 6 months after ESWT. 1,2 Another study suggested that optimal VAS score reduction and symptom improvement is offered by middle-energy ESWT compared with low-energy ESWT (level 3 evidence), especially with long-term results. 1 All 4 studies using exercise or rehabilitation found clinical improvement posttreatment.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…1,2 Another study suggested that optimal VAS score reduction and symptom improvement is offered by middle-energy ESWT compared with low-energy ESWT (level 3 evidence), especially with long-term results. 1 All 4 studies using exercise or rehabilitation found clinical improvement posttreatment. 10,12,30,39 Rehabilitation aimed at restoring scapular muscle balance, decreasing pain, and improving rotator cuff strength.…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical examination findings include audible, palpable, and/or painful crepitus of the scapulothoracic articulation during active shoulder movements [1,7,13]. Despite the etiology of SSS, nonoperative treatments are warranted first, prior to considering surgery [1,13,14].…”
Section: Introductionmentioning
confidence: 99%